A study on the climate change impacts of temperature on the built environment in Singapore - Setiawan Lie, Eryan (2016)
Today, climate change has been a global issue. Many natural extreme events have taken place, from the rise of sea level to the rapid melting of mountain glaciers. One factor that contributes to these events is the rise of temperature. Building structures are found to be more vulnerable with cracks appearance. It may be the result of the thermal movement from the expansion and contraction activities within the structural members. With the guidelines of Eurocode 1, numerical analysis is done to illustrate the thermal effects. Significant amount of stresses built is found and it is recommended to take the thermal action to be one of the important factors in the design calculation. A numerical analysis on a simply supported structure is used in this report. Eurocode 1, part 5 on the thermal actions is used closely as the guidance. Necessary parameters such as the maximum temperature from Singapore are extracted from the National Annexes. Comparison of the numerical analysis is then made with another country which has slightly higher temperature. As Singapore’s temperature is predicted to rise, adoption of higher parameters in its National Annexes may be necessary to avoid under design of the structural members. Recommendation of maximum temperature from Czech Republic can be used. Further experiments and studies shall be done to select the right value for the amendments.